A qualitative study of the views of patients with long-term conditions on family doctors in Hong Kong - Lo Yvonne YC; Lam Cindy LK; Hillier Sheila M; Siu Judy Y; Mercer Stewart W; Lam Tai; Griffiths Sian M (BMC Family Practice, 2010)
Abstract Background Primary care based management of long-term conditions (LTCs) is high on the international healthcare agenda, including the Asia-Pacific region. Hong Kong has a 'mixed economy' healthcare system with both public and private sectors with a range of types of primary care doctors. Recent Hong Kong Government policy aims to enhance the management of LTCs in primary care possibly based on a 'family doctor' model. Patients' views on this are not well documented and the aim of the present study was to explore the views of patients with LTCs on family doctors in Hong Kong. Methods The views of patients (with a variety of LTCs) on family doctors in Hong Kong were explored. Two groups of participants were interviewed; a) those who considered themselves as having a family doctor, b) those who considered themselves as not having a family doctor (either with a regular primary care doctor but not a family doctor or with no regular primary care doctor). In-depth individual semi-structured interviews were carried out with 28 participants (10 with a family doctor, 10 with a regular doctor, and 8 with no regular doctor) and analysed using the constant comparative method. Results Participants who did not have a family doctor were familiar with the concept but regarded it as a 'luxury item' for the rich within the private healthcare system. Those with a regular family doctor (all private) regarded having one as important to their and their family's health. Participants in both groups felt that as well as the more usual family medicine specialist or general practitioner, traditional Chinese medicine practitioners also had the potential to be family doctors. However most participants attended the public healthcare system for management of their LTCs whether they had a family doctor or not. Cost, perceived need, quality, trust, and choice were all barriers to the use of family doctors for the management of their LTCs. Conclusions Important barriers to the adoption of a 'family doctor' model of management of LTCs exist in Hong Kong. Effective policy implementation seems unlikely unless these complex barriers are addressed.